2018
DOI: 10.1002/ece3.3828
|View full text |Cite
|
Sign up to set email alerts
|

Life histories and ecotype conservation in an adaptive vertebrate: Genetic constitution of piscivorous brown trout covaries with habitat stability

Abstract: Ecotype variation in species exhibiting different life history strategies may reflect heritable adaptations to optimize reproductive success, and potential for speciation. Traditionally, ecotypes have, however, been defined by morphometrics and life history characteristics, which may be confounded with individual plasticity. Here, we use the widely distributed and polytypic freshwater fish species brown trout (Salmo trutta) as a model to study piscivorous life history and its genetic characteristics in environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 131 publications
(214 reference statements)
0
9
0
Order By: Relevance
“…Based on size at maturity, lake and sea feeding is superior to remaining within the river, albeit the relative importance of lake and sea feeding varies among catchments. If lacustrine S. trutta become piscivorous (Campbell, ; Wollebaek et al ., ), they can reach a larger size than anadromous conspecifics. Thus, in both Britain and Ireland, the largest rod‐caught piscivorous lacustrine S. trutta to date have had a greater mass than the largest anadromous S. trutta (Ferguson et al ., ), although the abundance of prey fish is such that only a small proportion of individuals can adopt piscivory (Campbell, ; Hughes et al ., ), compared with the greater abundance of prey fish at sea.…”
Section: Why Migrate and Where?mentioning
confidence: 98%
“…Based on size at maturity, lake and sea feeding is superior to remaining within the river, albeit the relative importance of lake and sea feeding varies among catchments. If lacustrine S. trutta become piscivorous (Campbell, ; Wollebaek et al ., ), they can reach a larger size than anadromous conspecifics. Thus, in both Britain and Ireland, the largest rod‐caught piscivorous lacustrine S. trutta to date have had a greater mass than the largest anadromous S. trutta (Ferguson et al ., ), although the abundance of prey fish is such that only a small proportion of individuals can adopt piscivory (Campbell, ; Hughes et al ., ), compared with the greater abundance of prey fish at sea.…”
Section: Why Migrate and Where?mentioning
confidence: 98%
“…It appears that in some cases both of these can occur in the same system. Wollebaek et al, (2018) for example, found genetic differentiation between piscivores and invertebrate feeders only in large tributaries and not in smaller ones of same catchment. These authors suggest that a genetically distinct piscivorous ecotype might be more likely to evolve in the relatively more stable large river habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Given that ferox forms have also been found elsewhere to be genetically distinct from other co-occurring trout (Duguid et al, 2006;Ferguson & Taggart, 1991), the evidence for a distinct ferox population in Loch Laidon is compelling. However, a recent paper suggests that feroxlike forms can also arise within genetic populations in some situations (Wollebaek, Heggenes, & Roed, 2018).…”
Section: Sympatric Population Structuringmentioning
confidence: 99%